Short-term intermittent hypoxia does not effect ventilation but reduces blood lactate concentration during submaximal exercise at simulated altitudes up to 4000 m - Faulhaber, M.; Dünnwald, T.; Gatterer, H.; Bernardi, L.; Burtscher, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Acute high-altitude exposure reduces endurance performance whereas chronic high-altitude exposure improves endurance performance at high altitude predominantly by ventilatory acclimatization (Burtscher et al. 2006). Intermittent hypoxia (IH), applying repeated passive hypoxic short-term (. 1 hour) exposures, induces ventilatory acclimatization by increasing the hypoxic ventilatory response (HVR). This increase in HVR seems to increase exercise ventilation and improve arterial oxygen saturation (SaO2) depending on the test altitude (Katayama et al. 2001, 2007). No study evaluated IH effects at different altitudes within the same group of persons. Therefore, we tested in the same group of persons whether IH affects submaximal exercise responses depending on different altitudes. Methods: Eight volunteers participated in the study (25±3 years, 179±4 cm, 74±5 kg). Measurements before IH included the determination of HVR and hypercapnic ventilatory response (HCVR) and 4 submaximal cycle ergometer tests at different simulated altitudes (1000m, 2000m, 3000m, and 4000m) in a randomized order. The subjects cycled for 10 minutes at 2 different work loads (corresponding to 40% and 60% of VO2max in normoxia). Ventilatory parameters, SaO2, and blood lactate concentrations (LA) were determined at each intensity. The subsequent IH application comprised 7 resting 1-hour sessions at 4500 m. Measurements after the IH application were the same as before and took place one day after finishing the IH application. Results: The applied IH protocol resulted in a significant increase in HVR whereas HCVR remained unchanged. Submaximal exercise ventilation was not affected, but carbon dioxide production and LA were reduced after IH independent of altitude. SaO2 improved slightly after IH. We found no interaction between the effects of altitude and those of IH. Discussion: Our results suggest that there are no ventilatory effects of the applied IH protocol during submaximal exercise at altitudes up to 4000 m. However, it might be possible that the effect of an increased HVR was opposed by the reduced blood lactate concentration and carbon dioxide output. Further research has to investigate if the reduced blood lactate concentrations result in an improved endurance performance at high altitude.